New species and previously unknown males of neotropical cleptobiotic stingless bees (hymenoptera, apidae, lestrimelitta) (2012)
Three new species of cleptobiotic stingless bees of the genus Lestrimelitta Friese, L. opita sp. n. and L. huilensis sp. n. from Colombia and L. catira sp. n. from Venezuela, are described and figured. The males of the Central American species L. chamelensis, L. danuncia, and L. mourei are also described and figured. New geographical records and an updated key to species from Central America and northern South America are provided.